Fundamentalism in Plural Campus (The Study of Christians Students in the Post Graduate Program Gadjah Mada University) - Flavius Florls Andrles (Balai Penelitian dan Pengembangan Agama Semarang, 2013)
The fundamentalism movement is getting increase and has considerable influence in the academic circumstance. This research aimed to understand how to reconstruct an ideas about religion and how its implementation in the religious movement on the campus. This qualitative research with in-depth interview techniques, and participant observation was found that the religious movements from KMK community of UGM Post Graduate has strong fundamentalism character and traits with following indicators: more oriented to the increase of exclusively religious spiritual values growth from the growth of academic intellectual values that able to compete in the mid of Science and Technology (IPTEK) development rate. The other things found in this research were not sufficient discourse on the implementation of theological values in the community. The religious teachings internalization process is using an indoctrination approach, so, the hermeneutic principles which the basis of the Bible interpretation process is ignored and finally the interpretation result were literal and fatal. On the other part there is PERKANTAS fundamentalism ideology influence that rooted in understanding the Bible literally affected the discourses in KMK community that eventually the religious understanding and movement has fundamental character.